The problem of asymmetric representation: The marginalisation, racialisation, and deservedness of Roma in Slovenia. (February 2023) - Zevnik, Andreja; Russell, Andrew
Special rights (such as a right to representation) are often used to address under-representation of minority and marginalised groups in political institutions. The case of Roma community in Slovenia is no different. Using a framework of social and political marginalisation, our article outlines asymmetry and exceptionality in the existing minority protection provisions for Slovenian Roma. We argue that the existing provisions are a consequence of majority's perception of Roma as racialised, marginalised, and undeserving group. We show that the limited access to special rights for Roma is not an oversight in the Slovenian democratic institutional design but a result of deep-rooted stereotypes and racialisation that this marginalised group is subjected to. More broadly, the case of Slovenian Roma demonstrates how principles of racialisation and marginalisation can help us understand absences of different marginalised minority groups from frameworks of special protection.